The philosophical dialogue as a tool of inquiry (Nóema, 2018)
Among the tools of philosophical work, the dialogue, as form of live "transaction" between two or more persons, seems to have its beginning and its end with Socrates. Along the subsequent development of our philosophical tradition the dialogue reappears only as literary genre. The essay aims to suggest that the live philosophical dialogue, if offered in new forms as a distributed social practice arranged and supported by the professional skills of philosopher, shows some promise of widening the boundaries of the examined life.
Keywords: Dialogue; philosophical practice; Socrates; communication